The Concept of Urban Capacity and Removal Processes-City Center Al-Najaf Al-Ashraf a Model - Al-Anazi, Maiaseh Mzhr; Al-shamari, Haitham Abdul Hussein (Al-Nahrain Journal for Engineering Sciences, 2025)
This study focused on the urban transformations resulting from the removal processes taking place in the urban fabric of sacred city centers, under the pretext of increasing urban capacity due to the density of use, which leads to the removal of important parts of the traditional urban fabric and adding them to the public urban space.To determine the amount of usage densities that the area can accommodate represented by the case study, which is the center of the holy city of Najaf: the study was based on using a quantitative measurement approach to test the hypothesis using a multivariable density measurement tool. A space matrix capable of measuring densities, accessibility, and diversity in the fabric during three time periods, a historical period 1900, 1990, and the current time 2024, to know the amount of changes that have occurred in the fabric. A qualitative measurement tool, which is a random sample questionnaire, was used to measure perceived density to find out which fabrics within the city center are more accommodating of congestion. The research has found that high and advanced accessibility through an integrated fabric with high connectivity that makes the city spaces work as one space leads to an increase in flows. It works to reduce the momentum in the city center and thus preserve the traditional urban fabric that must be emptied for pedestrians, as it represents the only fabric with The human scale at the level of the city as a whole (i.e. a fabric that is comfortable for pedestrians) also represents the identity of the area, and to accommodate the densities, the percentage of building density must be increased outside the traditional fabric.